2001
DOI: 10.1007/s004040000108
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression before and after the menopause

Abstract: Depression rate is significantly higher in menopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 12 publications
1
21
2
Order By: Relevance
“…Becht et al [77] reported that the Edinburgh Depression Scale is effective and user-friendly in the detection of depressive symptoms, and is not influenced by menopause-related somatic symptoms. The Beck Depression Inventory and State Trait Anxiety Inventory I and II have also been used [78]. It is important to note, however, that certain criteria identified by these scales may overlap in depressed individuals and those in perimenopause, making diagnosis difficult.…”
Section: Clinical Findingsmentioning
confidence: 99%
“…Becht et al [77] reported that the Edinburgh Depression Scale is effective and user-friendly in the detection of depressive symptoms, and is not influenced by menopause-related somatic symptoms. The Beck Depression Inventory and State Trait Anxiety Inventory I and II have also been used [78]. It is important to note, however, that certain criteria identified by these scales may overlap in depressed individuals and those in perimenopause, making diagnosis difficult.…”
Section: Clinical Findingsmentioning
confidence: 99%
“…A study by Sagsoz et al (11) revealed that the highest clinical signs of depression can be seen in women during postmenopause, when women suffer from hormonal changes in addition to physical and mental problems which may last for years.…”
Section: Introductionmentioning
confidence: 99%
“…Maartens et al (2002) also reported that psychotic symptoms such as depression, anger, somatization, and anxiety are frequent in menopausal women. Moreover, many clinical and epidemiological studies have found that the incidence rate of depression is higher in menopausal women, although the underlying reason is still unclear (Sagsoz et al, 2001). Researchers who ascribe menopausal depression to physiological mechanisms have presented a hypothesis that estrogen deficiency during menopause is the primary reason for menopausal depression, and they have attempted to show a causal relationship by showing the efficiency of estrogen supplement therapy in treating depression.…”
mentioning
confidence: 98%
“…Hay et al (1994) reported that the probability of experiencing depression within 4 years of menopause is 35%, and Sagsoz et al (2001) reported that menopausal women who experienced changes in menstruation commonly experience mental disorders such as depression and anxiety. Maartens et al (2002) also reported that psychotic symptoms such as depression, anger, somatization, and anxiety are frequent in menopausal women.…”
mentioning
confidence: 98%